2017
DOI: 10.1016/j.euf.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative 30-day Mortality Rates for Kidney Cancer Are Dependent on Hospital Surgical Volume: Results from a Norwegian Population-based Study

Abstract: The risk of dying within 30 d following kidney cancer surgery is low. Advanced disease and older age are risk factors for higher mortality. In this study, we also showed that more patients die within 30 d in hospitals performing fewer operations per year than in hospitals performing many operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…Historical studies showed conflicting results for short‐term nephrectomy morbidity and mortality trends over time . We found clear improvements in surgical mortality, with the 30‐day mortality rate decreasing to 1.1% in 2010, similar to the 0.9–2.7% reported by other countries during the same time period . The greatest improvements were seen in elderly patients aged ≥65 years, suggesting greater safety in surgery with reduced outcome inequality for patients of different ages and were consistent with the improvements seen in other urological procedures .…”
Section: Discussionsupporting
confidence: 82%
“…Historical studies showed conflicting results for short‐term nephrectomy morbidity and mortality trends over time . We found clear improvements in surgical mortality, with the 30‐day mortality rate decreasing to 1.1% in 2010, similar to the 0.9–2.7% reported by other countries during the same time period . The greatest improvements were seen in elderly patients aged ≥65 years, suggesting greater safety in surgery with reduced outcome inequality for patients of different ages and were consistent with the improvements seen in other urological procedures .…”
Section: Discussionsupporting
confidence: 82%
“…It is well‐known that RAPN is technically challenging and associated with a significant risk of complications, albeit this complication rate remains lower than the open approach . Despite many studies having assessed the relationship between provider volume and RAPN outcomes , to our knowledge no study to date has analysed both HV and SV.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of hospital volume on RCC patient outcomes has been a subject of interest and well characterised in widespread publications in recent years [12][13][14][15]. Most of these studies have concluded that higher hospital volume correlates to better outcomes particularly during the perioperative period.…”
Section: Discussionmentioning
confidence: 99%